Capitalist greed, pandemic and the future of social policy - Pereira, Camila Potyara; Potyara Amazoneida (Argumentum, 2021)
This text analyzes the harmful implications of the COVID-19 pandemic for social policy as a right of citizenship. Therefore, it demarcates the current global capital system, with its endless structural crisis, as the founding element of these implications. It incorporates emerging or under-visited themes and approaches, such as climate change, to broaden the conventional analytical scope and add to it with new factual and theoretical contributions. In this context of a double lethal crisis against humanity, the social policy guided by the commitment to the satisfaction of human needs, undergoes a violent reversal: it reduces itself to satisfying the needs for profit of capital, becoming averse to democratic sociability.